Guilty aesthetic pleasures - Aubry, Timothy Richard, 1975- (Harvard University Press, 2018)
Literary studies' turn to politics in the wake of the radical social movements of the 1960s and 1970s supposedly meant the banishment of aesthetic considerations from the academy. As scholars asked what role literary works played in supporting or challenging dominant ideologies, a focus on the text's formal beauty and the pleasures it might elicit came to seem irresponsible or even complicit with the iniquities of the social order. Until quite recently, this suspicion of aesthetics was the default posture within literary scholarship, a means of establishing the rigor of one's thought and the purity of one's political commitments. And yet the widely accepted view that the discipline simply changed directions at some point in the final decades of the twentieth century cries out for further scrutiny. With many scholars advocating a renewal of attention to textual surfaces and aesthetic experiences, it is worth asking whether the break with midcentury formalism was quite as clean is it once appeared. Tracing the succession of methodologies from New Criticism to the digital humanities, Guilty Aesthetic Pleasures retells the discipline's history from a new vantage point, with the aesthetic as the complicated, morally ambiguous, and embattled, but stubbornly resilient protagonist.--